(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
There is evidence that the purple nutsedge (Cyperus rotundus L.) aqueous extract can induce the plants rooting due to the high auxin concentrations. This study aimed to evaluate the effect of application seasons and concentrations of purple nutsedge aqueous extract application on the growth and production of carrot, cultivar Brasília. The experimental design was in randomized blocks, in a 2 x 5 factorial scheme in two seasons of the extract application (25 and 50 days after sowing) and five concentrations of (0%, 10%, 20%, 30% and 40%) with four replicates. Harvesting was carried out at 90 days after sowing, being evaluated the following morphological parameters: root diameter (cm); root fresh mass (g plant-1); plant height (cm); aerial part fresh mass (g plant-1); root dry mass (g plant-1); aerial part dry mass (g plant-1); plant dry mass (g plant-1); ratio between root dry mass and aerial part dry mass; root length (cm); commercial productivity (t ha-1); defective root mass (t ha-1); total productivity (t ha-1); commercial yield (roots kg-1); and root classification by length. The extract application at 50th day was more efficient for the root diameter (3.37 cm); fresh root mass (120.7 g plant-1); root length (15.4 cm); commercial productivity (68.2 t ha-1); total productivity (73.6 t ha-1); and commercial roots (8.8 roots kg-1). Root classification by length showed a higher percentage in the 14 cm classification range. The parameters did not present significant differences in both seasons, at 25th and 50th days, respectively, for root dry mass (12.0 and 12.8 g plant-1), ratio between dry mass of roots and aerial part (1.66 and 1.57), and defective root mass (1.3 and 1.5 t ha-1).